The Effectiveness of the Implementation of the CES Test on the Seafarer Rating Selection Process at PT. Main Marine Equinox - Ronald Simanjuntak; Derma Watty Sihombing; Baihaqi (Meteor STIP Marunda, 2024)
To maintain the quality of seafarers who work on principal-owned ships in collaboration with PT. Equinox Bahari Utama, the company made various selections, one of which was by carrying out the CES Test. However, in its implementation, seafarers have difficulty answering the questions in the test because of the constraints of Maritime English, so the minimum score set by the ship's owner company that is quite high cannot be met. Meanwhile, ship owners and seafarers actually give a positive perception of the implementation of this test. So that the effectiveness of the implementation of CES Test in companies on the selection process of rating seafarers needs to be measured and reviewed. This research is a type of research with a quantitative method. Data collection was carried out with a questionnaire distributed to 39 respondents, namely rating seafarers who had carried out the CES Test in the selection process at PT. Equinox Bahari Utama with a total of 17 statements. In looking for the results of data calculation and analysis, the author uses the SPSS version 21 program. In this study, it was found that the implementation of the CES Test in the selection process of rating seafarers at PT. The Main Marine Equinox runs ineffectively